Ide dalam Dinamika Kebijakan Kekerasan Anak di Provinsi Lampung - Febriani, Anita (PERSPEKTIF, 2024)
Inevitably, policies to eliminate violence against children in Lampung Province often change. These changes lead to continuous efforts to make improvements. These changes were deemed necessary because the results achieved did not meet the desired expectations. Policies that continue to change cannot be separated from the basic ideas. Ideas will become basic guidelines for developing changes to existing policies. This is the main aim of this research. This research will look at the basic ideas that influence policy changes. This research does not look at the efforts or role of local stakeholders. This research attempts to look at the historical context to see and analyze the basic ideas behind the dynamics of policies to eliminate violence against children in Lampung Province so far.  The research results show that the idea of ​​the dynamics of policies to eliminate violence against children in Lampung Province was influenced by the 1989 Convention On The Rights Of The Child agreement.